A Validated Stability Indicating RP-HPLC Method for the Determination of Aprepitant in Bulk and Pharmaceutical Dosage Forms - Bahlul Z.Awen2, Babu Rao Chandu2, Mukkanti Khagga3, Sreekanth Nama1*, (Recent Research in Science and Technology, 2010)
A stability indicating HPLC assay method has been developed and validated for the estimation of aprepitant in bulk and pharmaceutical dosage forms. A RP-HPLC isocratic separation was achieved on C18 column (250X4.6 mm i.d., 5µm) utilizing a mobile phase comprising of methanol and water in the ratio of 90: 10(v/v) and the eluents from the column were detected using a variable wavelength detector at 220 nm. The stress testing of aprepitant was carried out under acidic, alkaline hydrolysis, oxidation and thermal degradation (dry heat) conditions and apripitant was well resolved from its degradation products with good resolution. The proposed method has permitted the quantification of aprepitant in the linearity range of 1-100µg/ml and the flow rate was maintained at 1ml/min. The column was maintained at ambient temperature and the complete separation was achieved for aprepitant with all degradation products in an overall analytical run time of approximately 15 min and it was eluting at approximately 4.4 min. The retention times of aprepitant and rimonabant hydrochloride (IS) were found to be 4.383 min and 5.783 min, respectively. The limit of detection and limit quantification were found to be 0.130µg/ml and 0.395µg/ml, respectively. The percentage recovery was found to be in between 99.56 to 101.5 and the % RSD of system and method precision was found to be 1.20 and 0.561, respectively. The percentage amount of marketed commercial brand of aprepitant was found to be 99.97. The method was found to be suitable for the routine quality control analysis of aprepitant in bulk drug and formulation as well as for the stability indicating studies. The method was validated as per ICH guidelines.